Transformasi Manajemen Pendidikan Islam di Era Digital - Bustanul Arifin; Imron Fauzi; Mohammad Mahbub Junaidi; Rena Dwi Fitriani; Kuyatip; Fadly Usman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study explores the transformation of Islamic education management in the digital era, focusing on the strategies implemented and the challenges faced by Islamic educational institutions. The digital era brings significant changes in education management, where information and communication technology becomes the main pillar in supporting the teaching and learning process and education administration. This study uses a qualitative approach with a case study method in several Islamic educational institutions in Indonesia that have adopted digital technology in their management. The results of the study show that the transformation of Islamic education management in the digital era involves various innovative strategies, such as the implementation of an online learning management system (e-learning), curriculum digitalization, and the development of digital competencies for educators. However, the challenges faced are no less significant, including limited technological infrastructure, lack of digital literacy among educators and students, and resistance to change from some education stakeholders. This study concludes that the success of the transformation of Islamic education management in the digital era is highly dependent on the willingness of institutions to adapt and innovate, as well as adequate support from the government and society in overcoming the various challenges that arise. The implications of this study provide insight for Islamic education policy makers in formulating more effective strategies to face the dynamics of change in the digital era.